EVALUASI PEMAKAIAN VITAMIN D3 1000 IU SELAMA PANDEMI COVID-19 DI RUMAH SAKIT TK-II PUTRI HIJAU MEDAN - Modesta Harmoni Tarigan; Christica Ilsana; Sri Multerisnawati Lubis (Universitas Haji Sumatera Utara, 2022)
Large variations in COVID-19 mortality rates between countries and regions have been reported. In addition to age, comorbid diseases, and availability of health facilities; Vitamin D3 adequacy status is assumed to play a role, considering that the COVID-19 mortality rate was found to be relatively higher in countries with a high incidence of vitamin D3 deficiency, such as Italy, Spain, and France. Vitamin D3 has been shown to lower the risk of respiratory tract infections. At the same time, its effect in enhancing cellular and adaptive immunity also makes vitamin D3 worthy of consideration as a potential option for treating and preventing COVID-19. Sick Tk-II Putri Hijau Medan. This study uses a descriptive research method with a cross sectional approach with a retrospective research design, namely research by reviewing information or taking past data (Sugiyono, 2018). The data was obtained from prescriptions for the period February-April 2021. The results showed that there was an increase in the use of Vitamin D3 1000 IU, especially in moderate Covid 19 patients, as well as an increase in the use of Vitamin C 1000 mg and Vitamin C 500 mg. This is done with the aim of increasing the body's resistance when infected with Covid 19. In severe Covid 19 patients, vitamins are no longer given but rather are given anti-virus and anti-biotic treatment in the form of injections.